Perancangan User Interface Untuk Meningkatkan User Experience Menggunakan Metode Human Centered Design Pada Web E-Commerce CV. Cipta Karya Meubel Jepara - Kartiko Haryanto; Widiyanto Tri Handoko (LPPM STIKOM Tunas Bangsa, 2024)
E-commerce is the use of communication networks and computers to conduct business processes. Currently, many independent businesses facilitate sellers and buyers by providing convenience in digital transactions, including businesses in the furniture sales sector. With e-commerce, the target audience spans across different regions and generations, making furniture sales at CV. Cipta Karya Meubel not limited to the local population alone. CV. Cipta Karya Meubel Jepara requires an e-commerce platform with a user interface that is easily understandable by people from various backgrounds to enhance the user experience. To address and identify usability issues specifically, a user interface design process is needed, utilizing the Human-Centered Design method and evaluating usability using the Heuristic Evaluation (HE) method. This evaluation and design process is conducted to improve the comfort of using the e-commerce application. From the research findings, it can be concluded that the Human-Centered Design (HCD) and Heuristic Evaluation methods can simplify the application design process and align it with user needs.